Treatment of allergic rhinitis with acupoint herbal plaster: an oligonucleotide chip analysis - Shiue, Horng-Sheng (BMC Complement Altern Med, 2016)
BACKGROUND: Allergic rhinitis is regarded as an imbalanced Th1/Th2 cell-mediated response. The present study used microarray analysis to compare gene expression levels between allergic rhinitis patients before and after a series of acupoint herbal plaster applications. METHODS: In this experimental pilot study, volunteers experiencing sneezing, runny nose, and congestion for more than 9 months in the year following initial diagnoses were included after diagnostic confirmation by otolaryngologists to exclude patients with sinusitis and nasal polyps. Patients with persistent allergic rhinitis each received four acupoint herbal plaster treatments applied using the moxibustion technique. Clinical outcomes were evaluated using the Rhinitis Quality of Life Questionnaire (RQLQ). Peripheral blood samples were analyzed using an ImmunoCAP Phadiatop test, and patients were classified as phadiatop (Ph)-positive or -negative. Microarray results were analyzed for genes that were differentially expressed between (1) Ph-positive and -negative patients treated with herbal plaster; and (2) before and after herbal plaster treatment in the Ph-positive patient group. Unsupervised and supervised methods were used for gene-expression data analysis. RESULTS: Nineteen Ph-positive and four Ph-negative participants with persistent allergic rhinitis were included in the study. RQLQ results indicated that the 19 Ph-positive volunteers experienced improvement in six of seven categories following acupoint herbal plaster treatments, whereas the four Ph-negative participants reported improvement in only two categories. Hierarchical clustering and principle component analysis of the gene expression profiles of Ph-positive and –negative participants indicated the groups exhibited distinct physiological responses to acupoint herbal treatment. Evaluation of gene networks using MetaCore identified that the “Immune response_IL-13 signaling via JAK-STAT” and the “Inflammation_Interferon signaling” were down- and up-regulated, respectively, among Ph-positive subjects. CONCLUSIONS: In this preliminary study, we find that the IL-13 immune response via JAK-STAT signaling and interferon inflammation signaling were down- and upregulated, respectively, in the Ph-positive group. Further studies are required to verify these pathways in Ph-positive patients, and to determine the mechanism of such pathway dysregulation. TRIAL REGISTRATION: ClinicalTrials.gov: NCT02486159. Registered 30 Jun 2015.